"Formation of Legal Awareness and Legal Culture in Youth: A Priority Direction of the Education System" (Open Academia: Journal of Scholarly Research, 2025)
This article focuses on the necessity of conducting specific scientific research on elevating the legal awareness, legal culture, and public oversight to a new level, especially in terms of effectively utilizing these tools in the fight against corruption. It emphasizes the need to prioritize this issue within the framework of the state's policy